Obesity and sleep apnea are independently associated with adverse left ventricular remodeling and clinical outcome in patients with atrial fibrillation and preserved ventricular function - Shah, Ravi V. (Am Heart J, 2014)
AIMS: Obesity is associated with the development of atrial fibrillation (AF), and both obesity and AF are independently associated with the development of heart failure with preserved ejection fraction. We tested the hypothesis that sleep apnea (SA) would have a body mass index (BMI) independent association with adverse left ventricular (LV) remodeling and clinical outcomes in patients with AF and preserved LV function. METHODS AND RESULTS: From 720 consecutive patients with AF, 403 patients without myocardial disease (preserved LV function) were identified and followed up for 3.3 ± 1.5 years. The primary outcome was a combination of all-cause mortality/heart failure hospitalization. Left ventricular mass and LV mass-to-volume ratio were higher in patients with SA and obesity (P < .0001 for all). Body mass index (β per log = .47; P < .0001) and SA (β = .05; P = .045) were independently associated with LV mass index. Patients with treated SA had a lower LV mass index (but not LV mass-to-volume ratio) compared with untreated (P = .002). In a best overall multivariable model, SA therapy (β = −.129; P = .001) and BMI (β per log = .373; P = .0007) had opposing associations with LV mass index. Sleep apnea (hazard ratio [HR] = 2.94; P = .0004) and BMI (HR per 1 kg/m(2) = 1.08; P = .004) were associated with clinical outcome in unadjusted analysis. Only SA was associated with clinical outcome in a best overall multivariable model (HR = 2.14; P = .02). CONCLUSION: Sleep apnea and obesity are independently associated with adverse LV remodeling and clinical outcomes in patients with preserved LV function, whereas continuous positive airway pressure therapy is associated with a beneficial effect on LV remodeling. Research investigating SA therapies in patients at high risk for LV remodeling and heart failure is warranted.